IMPLEMENTATION OF RELIGIOUS CONFLICT RESOLUTION AND INTERFAITH HARMONY IN JAILOLO, WEST HALMAHERA - Tohe, Ansar; Abu Sahman Nasim,; Nursinita Killian,; Rahmat Libohongi, (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2025)
This study examines the resolution of interreligious conflicts in Jailolo, North Maluku, against the backdrop of social unrest with ethno-religious (SARA) nuances that erupted in various regions of Indonesia, such as the Ambon conflict (1998), Poso (1998), North Maluku (2000), Tobelo (the “Papilo Bloodshed” and “Sosol Bloodshed”), as well as Loloda and Kao-Malifut. These conflicts claimed numerous victims from both Muslim and Christian communities and severely disrupted local social and cultural harmony. The research aims to identify the background of the conflicts, the resolution strategies undertaken, the patterns of interreligious relations after the conflicts, and community responses to conflict resolution based on local wisdom. Employing a qualitative approach and inductive method, the findings reveal that Jailolo, with its pluralistic cultural and religious background, has adopted the local symbol Marimoi Ngone Foturu (“unity is strength”) as a social adhesive. This principle serves as both a conflict resolution tool and a model for post-conflict interreligious harmony. The study highlights that economic and political disparities initially triggered the conflicts, while religious issues emerged later, underscoring the importance of inclusive religious values and local wisdom in strengthening conflict resolution in Indonesia.